PENGARUH PERKEMBANGAN PASAR ASURANSI JIWA TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA MENGGUNAKAN ANALISIS REGRESI - Iin Irianingsih; Dwi Susanti; Nibros Komara; Muhamad Deni Johansyah; Badrulfalah Badrulfalah (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2019)
Life insurance is a contractual agreement between the policy holder or the insured and the insurance company as the guarantor and the insurance company will pay a nominal amount of money if there is a risk of death to the insurance policy holder. Insurance has been going on in Indonesia since the Dutch colonial era. The growth of insurance awareness is certainly inseparable from the influence of increasing public income which is at the same time an indication of economic growth. Regression analysis is a statistical technique used to study and model the relationships between research variables. This study discusses the influence of the development of the life insurance market on economic growth in Indonesia in the 2003-2017 period. The method used is a multiple linear regression model with independent variables are Life Insurance Penetration (LIP) and Life Insurance Density (LID), while the dependent variable is per capita Real Gross Domestic Product (RGDP). Based on the results of the analysis it was found that LIP significantly had a negative effect on RGPD per capita, while LID significantly had a positive effect on RGDP per capita.